2015
DOI: 10.1083/jcb.201410095
|View full text |Cite
|
Sign up to set email alerts
|

WISp39 binds phosphorylated Coronin 1B to regulate Arp2/3 localization and Cofilin-dependent motility

Abstract: WISp39 associates with Hsp90, Coronin 1B, and Slingshot phosphatase to regulate Cofilin activation and Arp2/3 complex localization at the leading edge of migrating cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…This effect was similar to that of cells lacking Coronin 1B, an F-actin-binding protein that is localized to the leading edge of migrating fibroblasts (35). Cells that lacked PLEKHG3 had a longer shape, similar to that observed in cells lacking other well-known proteins, such as Cofilin (36) or WISp39 (37), that are localized to the leading edge. There was no significant difference in the actin structures of the H9 and PLEKHG3 −/− cells.…”
Section: Discussionsupporting
confidence: 59%
“…This effect was similar to that of cells lacking Coronin 1B, an F-actin-binding protein that is localized to the leading edge of migrating fibroblasts (35). Cells that lacked PLEKHG3 had a longer shape, similar to that observed in cells lacking other well-known proteins, such as Cofilin (36) or WISp39 (37), that are localized to the leading edge. There was no significant difference in the actin structures of the H9 and PLEKHG3 −/− cells.…”
Section: Discussionsupporting
confidence: 59%
“…F-actin disassembly and/ or severing via ADF/cofilin yields polymerization competent monomers 12,34 as well as yielding free polymerization-competent barbed ends. 35,36 The role of the cofilin phosphatase Slingshot 37,38 and the coronin 39 family of proteins may be major factors in sensing F-actin and in regulating the size of the G-actin pool. Furthermore, the activities of cofilin and the Arp2/3 complex are synergistic 34,40 and both are required for proper lamellipodia function, [41][42][43] so it seems that polymerization-competent actin generated by disassembly near membranes may be primed for the nucleation of new daughter filaments.…”
Section: Competition and Collaboration Between Different Actin Assembmentioning
confidence: 99%
“…Our recent study has revealed two new important players in cellular motility. We have found that WISp39 (Waf1 Cip1 stabilizing protein 39), an Hsp90 binding protein we had discovered [ 4 ], coordinates Coronin 1B, Arp2/3 complex and Cofilin activity in the lamellipodia to achieve directed cell motility [ 5 ]. WISp39 is recruited to actin-enriched cell protrusions which contain the Arp2/3 complex and Coronin 1B.…”
mentioning
confidence: 99%
“…WISp39 is recruited to actin-enriched cell protrusions which contain the Arp2/3 complex and Coronin 1B. Its knockdown results in the loss of directional motility and cell polarity, accompanied by profound changes in cell morphology [ 5 ]. Rescue of WISp39 function in WISp39 siRNA-treated cells restores directionality of motility to control levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation